Fragmentary Prose of O. Kobylianska: the Specifics of Literature Forming of World - Матвєєва, Тетяна Степанівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The object of the paper is the fragmentary prose of O. Kobylianska.The subject of the study is semantic- and form-making components, genre specifics of works (intermediality, intergeneric synthesis).The sphere of observation is problem-thematic complexes, images, images-symbols. Semantic filling of autor’s motto, allusions (mostly mythological, biblical, literary), context planes (cultural, artistic).The particular aspect is aesthetic paradigm, in the light of which the artist represents the world in its simultaneously manifested objectivity/symbolicalness. The type and peculiarities of presentation, mechanisms of artistic realization of dichotomy world/human, interconnection or seizure in dyads Me/Me, Me/The Other are also studied.Methods and means of text structuring are analyzed. Antithetic, gradation, contrast methods, a method of plot reduction, reflectivity, compositional circle are mentioned among chief ones.Basing on the definition of main genres of fragmentary prose – sketch, outlines – the characteristics of genre form of works under analysis are grounded.It is concluded about the place of fragmentary prose in the writer creative activity, particularly about common poetical resolutions in the field of novel study.